PELELANGAN OBJEK PERJANJIAN GADAI EMAS ANTARA NASABAH DENGAN BANK BRI SYARIAH CABANG PEKANBARU - Rahmanila, Rahmanila; Bachtiar, Maryati; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Gold Pawn is one of the BRI Syariah Syariah products which is included in thecategory of financing based on al-qardh (giving), the funds must be returned by the customerto the bank at the same time or in installments up to the due date and implemented byapplying the prudent bankking principle ) as well as the principle of getting to knowcustomers (know customers). In practice, in the procedure for settlement of collateral itemsdue at BRI Syariah Bank, contact the Customers whose loan maturity is due, the 4th day afterthe maturity of the loan. Purpose Writing this thesis, namely: First, to find out the procedurefor auctioning the object of the gold pawning agreement between customers and BRI SyariahBank Pekanbaru Branch. Second, to find out the legal protection of customers auctioning theobject of the gold pawning agreement at BRI Syariah Bank Pekanbaru Branch.This type of research can be classified as a type of sociological legal research,because in this study the authors directly conduct research on the location or places that arestudied to provide a complete and clear picture of the problem under study. This researchwas conducted at BRI Syariah Bank Pekanbaru Branch, while the population and samplewere all sections related to this research, the data sources used were primary data,secondary data and tertiary data, data collection techniques, namely interviews andliterature studies.From the results of research and discussion it can be concluded that, in the goldauction procedure at PT. BRI Syariah Bank Pekanbaru Branch has not used Minister ofFinance Regulation No. 93 /PMK.06/2010 concerning Bidding Implementation Guidelines.The bank still uses the guidelines for conducting auctions made by the directors of PT. BankBRI Syariah Pusat. Which in Article 2 of the PMK 2010 states that: Every auction must becarried out by and / or in front of the Auction Officer. The legal protection of customers asconsumers is listed in the Civil Code in Article 1155 which states that collateral itemsauctioned will be auctioned before the public and in accordance with applicable regulationsso as not to cause harm to customers.Keywords: Auction of Gold Pawn Agreement Objects at BRI Syariah Bank.